JAM-A overexpression is related to disease progression in diffuse large B-cell lymphoma and downregulated by lenalidomide - Peng-Peng Xu (Nature Portfolio, 2017)
Abstract Cancer stem cells play an important role on tumor progression. Biomarkers of stem cell property and their relationship to extranodal involvement of malignant lymphocytes are undefined in diffuse large B-cell lymphoma (DLBCL). Here we showed that junctional adhesion molecule-A (JAM-A) was highly expressed in DLBCL patients with multiple extranodal lesions. JAM-A maintained B-lymphoma cell stemness and was associated with cell invasion and epithelial-to-mesenchymal transition both in vitro and in vivo. As mechanism of action, JAM-A overexpression selectively activated transforming growth factor-β (TGF-β)/NODAL signaling, thereby enhanced B-lymphoma cell aggressiveness and induced extranodal involvement to mesoendoderm-derived organs in DLBCL. Lenalidomide downregulated JAM-A and downstream NODAL expression, resulting in inhibition of B-lymphoma cell invasion and epithelial-to-mesenchymal transition. In a murine xenograft model established with subcutaneous injection of JAM-A-overexpressing B-lymphoma cells, lenalidomide retarded tumor growth and prevented cell invasion to mesoendoderm-derived organs, consistent with the downregulation of JAM-A and NODAL expression. Collectively, these findings indicated that JAM-A was related to extranodal involvement in DLBCL through modulating TGF-β/NODAL signaling. Identified as a biomarker of stem cell property, JAM-A indicated the sensitivity of B-lymphoma cells to lenalidomide. Therapeutic targeting of JAM-A/NODAL axis could thus be a promising clinical strategy to impede tumor progression in DLBCL.